Exploring the relationship between health literacy and attitude to believe fake news about food: a survey among the Italian population - Guglielmo Bonaccorsi; Rosa Prato; Francesca Fortunato; Pier Luigi Lopalco; Valeria Gabellone; Fabiana Nuccetelli (BMJ Nutrition, Prevention & Health)
Objectives To examine the correlation between health literacy (HL) and susceptibility to food-related fake news, and to explore the role of social media and influencers in shaping consumers’ food choices.Design Cross-sectional survey conducted via an online questionnaire.Setting Nine community pharmacies located in northern, central and southern Italy.Participants A total of 2284 consumers recruited between January and March 2024.Results Lower HL levels were significantly associated with poorer self-reported education, health and economic status, as well as precarious employment. These same variables were linked to a higher likelihood of believing and spreading food-related fake news. Individuals from socioeconomically disadvantaged backgrounds were also more likely to trust influencers who influenced their food choices.Conclusions HL plays a key role in reducing the susceptibility to food-related misinformation, particularly in lower socioeconomic groups. Targeted interventions aimed at improving HL may help mitigate the spread of fake news and empower individuals to make healthier food choices.